A Short Review on the Relationships Between Nephrolithiasis and Myocardial Infarction : - Karami, Hormoz; Maleki, Hadi; Baghbeheshti, Maryam; Hashemi, Mostafa; Rouzbeh, Mehrdad; Afkhami Ardakani, Mohammad (Galen Medical Journal, 2019)
The interaction between organs is a crucial part of modern medicine. As a very prerequisite to manage a disease, practitioners should have a full awareness of the related organs. Kidney and heart are two vital organs that are closely interconnected in various fields. These two organs have a lot of common risk factors for making a person unhealthy; therefore, if you prevent the disease in one of them, the other’s morbidity might be alleviated as well. Among them, nephrolithiasis and myocardial infarction (MI) have more risk factors in common, and both could be fatal. Also, these two diseases are important regarding the prevalence, incidence, and burden of disease. Some studies confirm the relationship between MI and nephrolithiasis; however, further researches are needed to discover the exact direction of their relationship. The present review aims to explain the mechanism of MI and nephrolithiasis; clarify the relationship between these two disease based on physiological, pathological, and clinical studies; and propose some solutions for the prevention and treatment of such diseases. [GMJ.2019;8:e1289]